A day to smile life - Alain Manuel Chaple Gil (Editorial Ciencias Médicas, 2015)
Since 2013, the planet celebrates World Oral Health Day on March 20. The original date of this celebration was September 12, but it was modified because it coincided with other international commemorations, such as the Annual Congress of the International Dental Federation (FDI). We could ask ourselves, what does the new date mean? Children have 20 temporary teeth; adults statistically have at least 20 natural permanent teeth at the end of their lives; if the date is expressed numerically, first the month and then the day we have 3/20. At the same time, the reading of these digits indicates the formula of a healthy mouth in an adult: 32 teeth and 0 dental caries. Cuba celebrated this day for the first time in this year 2015. On the occasion of the date, conferences, courses and round tables were held with the participation of prestigious professors. They were days full of health education promotion, contests and smiles of children, adolescents and adults that have contributed to the development of Cuban Stomatology. Organized by the Cuban Society of Stomatology, the event aims that stomatological science and joy are founded for the well-being of our people. Let the future give smiles for all the days of the year.